Cu-Ni alloys coatings for corrosion protection on mild steel in 0.5 M NaCl solution / Mohammad Hafizudden Mohd Zaki, Yusairie Mohd and Nik Norziehana Che Isa - Mohd Zaki, Mohammad Hafizudden; Mohd, Yusairie; Che Isa, Nik Norziehana (2017)
Mild steel is the most common metal used in industry. However, mild steel easily corrodes when exposed to environment. One way to protect mild steel from corrodes is by coating it with more noble metal like copper and its alloys. In this study, copper and Cu-Ni alloys were successfully coated on the mild steel substrate by electrodeposition technique using alkaline citrate solutions containing Cu and Ni ions precursors. The reaction and mechanisms of the electrodeposition of copper and Cu-Ni alloys on the mild steel substrate were investigated by cyclic voltammetry and chronoamperometry methods. Surface morphology of the coatings was examined by FESEM. The elemental compositions of the coatings were confirmed by EDAX analysis. The molar ratios of Cu-Ni solutions have affected the formation of the coatings. Corrosion study shows that copper coated mild steel canimprove the corrosion resistance of the mild steel in 0.5 M NaCl. Cu-Ni coating prepared from Cu60-Ni40 showed the highest corrosion resistance. The order of the corrosion resistance of the samples in 0.5 M NaCl at 25 oC is Cu60-Ni40> Cu75-Ni25> Cu90-Ni10> Cu100> mild steel.